The protein effect in the structure of two ferryl-oxo intermediates at the same oxidation level in the heme copper binuclear center of cytochrome c oxidase - Pinakoulaki, Eftychia; Daskalakis, Vangelis; Ohta, Takehiro; Richter, Oliver Matthias H; Budiman, Kerstin; Kitagawa, Teizo; Ludwig, Bernd; Varotsis, Constantinos (My University, 2013)
Identification of the intermediates and determination of their structures in the reduction of dioxygen to water by cytochrome c oxidase (CcO) are particularly important to understanding both O2 activation and proton pumping by the enzyme. In this work, we report the products of the rapid reaction of O2 with the mixed valence form (CuA2+, heme a3+, heme a32+-Cu B1+) of the enzyme. The resonance Raman results show the formation of two ferryl-oxo species with characteristic Fe(IV)=O stretching modes at 790 and 804 cm-1 at the peroxy oxidation level (P M). Density functional theory calculations show that the protein environment of the proximal H-bonded His-411 determines the strength of the distal Fe(IV)=O bond. In contrast to previous proposals, the PM intermediate is also formed in the reaction of Y167F with O2. These results suggest that in the fully reduced enzyme, the proton pumping νFe(IV)=O = 804 cm-1to νFe(IV)=O = 790 cm-1transition (P→F, where P is peroxy and F is ferryl) is triggered not only by electron transfer from heme a to heme a3 but also by the formation of the H-bonded form of the His-411-Fe(IV)=O conformer in the proximal site of heme a3. The implications of these results with respect to the role of an O=Fe(IV)-His-411-H-bonded form to the ring A propionate of heme a3-Asp-399-H2O site and, thus, to the exit/output proton channel (H2O) pool during the proton pumping P→F transition are discussed. We propose that the environment proximal to the heme a3 controls the spectroscopic properties of the ferryl intermediates in cytochrome oxidases.
Keywords: Bioenergetics; Computation; Cytochrome Oxidase; Heme; Raman Spectroscopy